The three laws of performance rewriting the future of your organization and your life - Zaffron, Steve 1944- (Jossey-Bass, 2009)
When a hurricane warning is announced, everyone's concerns and actions become focused on that expectation; the hurricane essentially becomes the future which people are "living into." Similarly, when an organization needs to transform or make the leap to a higher level, everyone involved should be "living into" the vision of the organization's new, improved future. But in the majority of organizations, the future people are living into is based on past performance and experience, and so major transformation is almost impossible. Steve Zaffron is, CEO of Vanto Group which ha.
Includes bibliographical references (pages 209-210) and index. - Print version record
Keywords: Performance; Organization; Leadership; Performance technology; Organization and Administration; Task Performance and Analysis; Rendement au travail; Organisation; BUSINESS & ECONOMICS; Personal Success; BUSINESS & ECONOMICS; Careers; General